1997
DOI: 10.1093/nar/25.20.4147
|View full text |Cite
|
Sign up to set email alerts
|

The Neisseria gonorrhoeae S.NgoVIII restriction/modification system: a type IIs system homologous to the Haemophilus parahaemolyticus HphI restriction/modification system

Abstract: Strains of Neisseria gonorrhoeae possess numerous restriction-modification (R-M) systems. One of these systems, which has been found in all strains tested, encodes the S. NgoVIII specificity (5'TCACC 3') R-M system. We cloned two adjacent methyltransferase genes (dcmH and damH), each encoding proteins whose actions protect DNA from digestion by R.HphI or R.Ngo BI (5'TCACC 3'). The damH gene product is a N 6-methyladenine methyltransferase that recognizes this sequence. We constructed a plasmid containing multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Study of the closely related isolates from a Dutch family provides evidence that a population of H. pylori cells could regulate its R–M function by deletion from the chromosome and reacquisition by natural transformation and homologous recombination. The parallel organization of the hpy 188I R–M locus (Xu et al ., 2000b) suggests that this may be a general mechanism for H. pylori , and possibly for other naturally competent organisms that have direct repeats flanking R–M systems, such as Haemophilus parahaemolyticus (Lubys et al ., 1996; Gunn and Stein, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Study of the closely related isolates from a Dutch family provides evidence that a population of H. pylori cells could regulate its R–M function by deletion from the chromosome and reacquisition by natural transformation and homologous recombination. The parallel organization of the hpy 188I R–M locus (Xu et al ., 2000b) suggests that this may be a general mechanism for H. pylori , and possibly for other naturally competent organisms that have direct repeats flanking R–M systems, such as Haemophilus parahaemolyticus (Lubys et al ., 1996; Gunn and Stein, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Some restriction-modification gene homologues are found to be flanked by long (in the order of 100 bp) direct repeats (Lubys et al 1996;Gunn and Stein 1997;Nobusato et al 2000b;Aras et al 2001). The comparison of two genomes of H. pylori has suggested that this duplication is generated when a restriction-modification gene complex inserts itself into the genome (Fig.…”
Section: Insertion With Long Target Duplicationmentioning
confidence: 99%
“…Horizontal gene transfer of R-M systems between bacterial species has been described, and it has been suggested that this transfer contributes to the wide distribution of bacterial R-M systems (28). Examples for this phenomenon are sequence similarities between gonococcal and Haemophilus R-M systems (22,47).…”
mentioning
confidence: 99%